Lymph node biopsy analysis reveals an altered immunoregulatory balance already during the at‐risk phase of autoantibody positive rheumatoid arthritis - Ramwadhdoebe, Tamara H. (Eur J Immunol, 2016)
The balance between proinflammatory and regulatory CD4(+) T cells is tightly controlled in lymphoid organs. In autoimmune diseases this balance is altered in the periphery and target tissue of patients. However, not much is known about the balance initiated in lymphoid organs during the development of disease. Since systemic autoimmunity is present years before the clinical manifestations of rheumatoid arthritis (RA), it is possible to study the immunoregulatory balance during the earliest (preclinical) phases of disease. Here, we report for the first time the frequency and phenotype of proinflammatory and regulatory CD4(+) T cells in lymph node biopsies obtained from autoantibody positive individuals at risk for developing RA, patients with established disease and healthy controls. The frequency of proinflammatory LN Th1 cells was increased in RA patients compared with HCs, while the frequency of regulatory T cells was lower in LN biopsies of RA‐risk individuals. Upon in vitro stimulation LN CD4(+) T cells produced lower levels of proinflammatory cytokines, IFN‐γ and IL‐17A, in both RA‐risk individuals and early RA patients. This study shows that already during the earliest phases of systemic autoimmunity the immunoregulatory balance between proinflammatory and regulatory CD4(+) T cells is altered in LN tissue.